Computational Taxonomy for Identification of "Moving Groups". Applied to Open Clusters - Orellana, Rosa Beatriz (2010)
A new method is presented here to identify the members of an open cluster, based on computational taxonomy: “the spectral method”. The characters used for the analysis are position and proper motion of all the stars belonging to the cluster’s region. Taxonomy allows to groups the stars together (OTU’s) in clusters, based on its genotypic characteristic, which shows the similarity, between two or more Stars (OTU’s). The method has been applied to open cluster NGC2516. The outcome list of members agrees very well with the one obtained by applying other methods.